2022
DOI: 10.21203/rs.3.rs-2307366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A magnetic hydrogel for the efficient retrieval of kidney stone fragments during ureteroscopy

Abstract: Surgical management of stone disease aims for complete clearance, yet only 60–75% of ureteroscopic laser lithotripsy treatments achieve complete stone-free status. Up to 30% patients with residual fragments < 2 mm in size experience stone-related complications. We demonstrate a method of stone fragment retrieval in which fragments are coated with a magnetic hydrogel and retrieved en masse with a magnetic guidewire. The magnetic hydrogel facilitated robust in vitro capture of stone fragments up to 4 mm in si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In addition, this study also conducted in vitro tests by cultivating urethral inflammatory cells, and found that hydrogel components had no cytotoxicity in cell culture, and had certain antibacterial ability, and had only superficial effects on human urothelium in vitro and mouse bladder in vivo. This effective method of extracting kidney stone fragments can improve stone rate and patient prognosis [25]. At present, most methods of active removal of RF are to use a wire basket, introduce the encrusted stone through a ureteroscope, and remove it from the body.…”
Section: Novel Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study also conducted in vitro tests by cultivating urethral inflammatory cells, and found that hydrogel components had no cytotoxicity in cell culture, and had certain antibacterial ability, and had only superficial effects on human urothelium in vitro and mouse bladder in vivo. This effective method of extracting kidney stone fragments can improve stone rate and patient prognosis [25]. At present, most methods of active removal of RF are to use a wire basket, introduce the encrusted stone through a ureteroscope, and remove it from the body.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Methods are now emerging that focus on adhering RF to autologous blood clots or biopolymers to facilitate basket extraction. At present, the use of a magnetic extraction method has great prospects and greatly improves the stone expulsion rate, but further improvement is still needed, for example, studies have found that the use of catheter-based magnetic tools to magnetize kidney stones and recover them is limited by low magnetic strength [25].…”
Section: Novel Therapiesmentioning
confidence: 99%